Can half-a-monolayer of pt simulate activity like that of bulk pt? solar hydrogen activity demonstration with quasi-artificial leaf device - Bajpai, Himanshu; Patra, Kshirodra Kumar; Ranjan, Ravi; Nalajala, Naresh; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2020)
Pt is the best cocatalyst for hydrogen production. It is also well-known that the surface atomic layer is critical for catalysis. To minimize the Pt content as cocatalyst, herein we report on half-a-monolayer of Pt (0.5 theta(Pt)) decorated on earth-abundant Ni-Cu cocatalyst, which is integrated with a quasiartificial leaf (QuAL) device (TiO2/ZnS/CdS) and demonstrated for efficient solar hydrogen production. For the QuAL, TiO2 is sensitized with ZnS and CdS quantum dots by the SILAR method. The 0.5 theta(Pt)-decorated Ni-Cu shows an onset potential of 0.05 V vs reversible hydrogen electrode for the hydrogen evolution reaction, which is almost similar to that of commercial Pt/C. Photoactivity of the present QuAL device with either bulk Pt or 0.5 theta(Pt)-coated Ni-Cu cocatalyst is, surprisingly, equal. Our findings underscore that a fraction of a monolayer of Pt can enhance the activity of the cocatalyst, and it is worth exploring further for the high activity associated with atomic Pt and other noble metals.
Keywords: artificial leaf; nickel-copper; Photocatalysis; platinum; Solar hydrogen

Cu-Ni bimetal integrated TiO2 thin film for enhanced solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Saikia, Pranjal; Gopinath, Chinnakonda S. (Solar RRL, 2020)
A series of non-noble Cu-Ni bimetallic catalysts is prepared with different molar proportions of metals. Of these bimetallic catalysts, 1 wt% is subsequently integrated with titania P25. The catalysts are evaluated for solar hydrogen generation under 1 sun condition in both the powder and thin film forms. All the photocatalysts in the thin film exhibit an 8-24 times higher hydrogen yield (HY) compared with the corresponding particulate counterpart. The highest HY (41.7 mmol h(-1) g(-1)) is demonstrated for the photocatalyst Cu-Ni/TiO2 (CNT; 1:1 = Cu:Ni) in the thin film form, which is 24 times higher than that with its powder counterpart (1.75 mmol h(-1) g(-1)) and exceeds the performance of other Cu-Ni/TiO2 compositions. This enhanced activity in the thin film can be ascribed to improved absorption of visible light and an effective separation of photogenerated charge carriers at the interface of Cu-Ni/TiO2 leading to better charge carrier utilization.
Keywords: bimetals; energy conversion; Hydrogen; Photocatalysis; solar energy